Statement of Peer Review - Russel Torah; Kai Yang; Beckie Isaia; Paula Veske-Lepp; Frederick Bossuyt; Stephen Beeby (Engineering Proceedings)
In submitting conference proceedings to MDPI Engineering Proceedings, the volume editors of the proceedings certify to the publisher that all papers published in this volume have been subjected to peer review administered by the volume editors [...]